2019
DOI: 10.1093/nar/gkz805
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of cell death and proliferation in perturbation transcriptomics data—from confounding factor to effective prediction

Abstract: Transcriptional perturbation signatures are valuable data sources for functional genomics. Linking perturbation signatures to screenings opens the possibility to model cellular phenotypes from expression data and to identify efficacious drugs. We linked perturbation transcriptomics data from the LINCS-L1000 project with cell viability information upon genetic (Achilles project) and chemical (CTRP screen) perturbations yielding more than 90 000 signature–viability pairs. An integrated analysis showed that the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…While preparing this manuscript, a similar analysis was reported investigating the patterns of association between expression and viability using several of the same datasets [24]. The authors' results are largely concordant with our findings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…While preparing this manuscript, a similar analysis was reported investigating the patterns of association between expression and viability using several of the same datasets [24]. The authors' results are largely concordant with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…However, it is not guaranteed to capture cell-context-specific effects, and only a portion of these effects are likely to be associated with the resulting cell death or cell cycle arrest processes. By integrating measured viability data, our modeling approach explicitly decomposes the transcriptional response to a perturbation into a viability-related component (which could suggest a drug's killing mechanism), and a viability-independent component (which could better resolve the drug's MOA, as was recently shown [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, a wide variety of machine learning methods have been developed to help to understand the mechanisms underlying gene expression [ 1 , 16 ], and thus far some of previous published work has demonstrated that deep learning is an effective approach to connect signatures to prior knowledge such as side effects, indication, targets or drug sensitivity [ 1 , 16 19 ], and has Noted that the high hidden layer feature of deep learning could effectively reduce the batch effect [ 15 ]. Considering the usage of the existing tools limited by the high cost in computational resource and the difficulty in model training and accuracy evaluation, here we report a new efficient method for querying gene expression data by taking advantage of deep neural networks to learn an embedding and do more precision classification.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Szalai Bence et al conducted a model prediction analysis based on the correlation between the differentially expressed genes measured in the cell lines and the drug sensitivity under the action of the the drug at a specific concentration, and found that the cell line response was correlated with the drug concentration and time. However, the model achieved low accuracy and poor fitting in the prediction process because it ignored the non-linear characteristics between differentially expressed genes and the drug sensitivity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%